2022
DOI: 10.3390/ma15041421
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization Analyses of Low Brass Filler Biomaterial for Hard Tissue Implanted Scaffold Applications

Abstract: A biomaterial was created for hard tissue implanted scaffolds as a translational therapeutic approach. The existing biomaterials containing titanium dioxide filler posed a risk of oxygen gas vacancy. This will block the canaliculars, leading to a limit on the nutrient fluid supply. To overcome this problem, low brass was used as an alternative filler to eliminate the gas vacancy. Low brass with composition percentages of 0%, 2%, 5%, 15%, and 30% was filled into the polyester urethane liquidusing the metallic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Forero et al (2017) [ 53 ] used an electrical biosensor of CuZn, which was better than either Zn by Lestari et al (2018) or Cu by Wang et al (2018). They made a bone tissue engineering scaffold with the appropriate pore size, interconnection, and high porosity that was similar to that of our studies [ 54 ]. Natural API such as hydroxyapatite (HAp) was used in the CuZn/gelatin/chitosan (Chi) drug carrier for bone repair and regeneration, including mineralisation, collagen stimulation, osteoblast cell adhesion, and proliferation.…”
Section: Electrical Biosensors For Electrical Trigger In Drug Deliver...supporting
confidence: 53%
See 2 more Smart Citations
“…Forero et al (2017) [ 53 ] used an electrical biosensor of CuZn, which was better than either Zn by Lestari et al (2018) or Cu by Wang et al (2018). They made a bone tissue engineering scaffold with the appropriate pore size, interconnection, and high porosity that was similar to that of our studies [ 54 ]. Natural API such as hydroxyapatite (HAp) was used in the CuZn/gelatin/chitosan (Chi) drug carrier for bone repair and regeneration, including mineralisation, collagen stimulation, osteoblast cell adhesion, and proliferation.…”
Section: Electrical Biosensors For Electrical Trigger In Drug Deliver...supporting
confidence: 53%
“…These multivalent ions are crucial for the human body’s biocatalytic reactions [ 46 ]. Furthermore, Cu bonded with polyester via nitrogen (N) to form a LROP structure, which was illustrated in our previous study of structural characterization, as shown at the right of Figure 2 [ 54 ]. Thus, this Cu had a similar function to the inert metal ion (Zn 2+ ) that was linked by an active ligand in LROP.…”
Section: Other Stimuli and Chemotherapiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The structural characteristics of biomaterial had been studied in our previous article [60]; thus, this low brass filler composition weight percentages in biomaterial was the focus of this study. An attempt was made to investigate the low brass filler's role in these reversible continuous dynamic recrystallization mechanisms of biomaterials.…”
Section: Morphology Analysismentioning
confidence: 99%
“…For the last experimental work, a biomaterial was fabricated using the metallic filler polymer reinforced method [ 44 , 45 , 46 ] to provide the requisite mechanical and structural strengths [ 47 ] for the scaffold integrity [ 48 ]. The tensile strength and flexural strength for this biomaterial made of 30% low brass filler and 70% polyester urethane liquid were found to be 203 MPa and 1015 MPa, respectively [ 18 , 49 ]. Although there was a different nominal composition between the cart brass (70% copper and 30% zinc) and low brass (80% copper and 20% zinc), the maximum tensile and yield strengths for both brass products were the same [ 50 ].…”
Section: Simulation Results Analysesmentioning
confidence: 99%